2018
DOI: 10.3389/fcimb.2018.00232
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Porcine Circovirus Type 2 Chimeric VLPs (cVLPs) Displays Foreign Peptides on the Capsid Surface

Abstract: Although porcine circovirus-like particles can function as a vector to carry foreign peptides into host cells, displaying foreign peptides on the surface of virus-like particles (VLPs) remains challenging. In this study, a plateau, consisting of the middle portion of Loop CD (MP-Lcd) from two neighboring subunits of PCV2 capsid protein (Cap), was identified as an ideal site to insert various foreign peptides or epitopes and display them on the surface of PCV2 VLPs. One of the goals of this work is to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition, PCV2 VLPs have also been extensively used to study the structure of the PCV2 capsid (4, 5), PCV2 binding receptors on cell surface (27), PCV2 entry and infection (28,29), as well as the mechanism of the PCV2 capsid assembly (30). In addition, PCV2 VLPs have been used as a vehicle to display various foreign epitopes or functional peptides in vivo (31)(32)(33)(34). Understanding the mechanism of PCV2 VLP assembly will also greatly advance applications of the VLPs as a novel multivalent vaccine and a vector for gene delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PCV2 VLPs have also been extensively used to study the structure of the PCV2 capsid (4, 5), PCV2 binding receptors on cell surface (27), PCV2 entry and infection (28,29), as well as the mechanism of the PCV2 capsid assembly (30). In addition, PCV2 VLPs have been used as a vehicle to display various foreign epitopes or functional peptides in vivo (31)(32)(33)(34). Understanding the mechanism of PCV2 VLP assembly will also greatly advance applications of the VLPs as a novel multivalent vaccine and a vector for gene delivery.…”
mentioning
confidence: 99%
“…The eight ␤-strands are connected by seven loops (loops BC, CD, DE, EF, FG, GH, and HI), which contribute to the PCV2 surface features (except loop FG) and stabilize the capsid via extensive interactions with neighboring loops (35). Loop CD is exposed on the capsid surface and frequently exploited as a site to display foreign epitopes on the surface for multivalent vaccine design (33,34). In loop DE, a unique cysteine was reported to play a critical role in the assembly of PCV2 VLPs since the point mutant (C108S) failed to self-assemble into VLPs in vitro (30).…”
mentioning
confidence: 99%
“…The crystal structure of the PCV2 virus-like particle (VLP) revealed that the capsid protein comprises two β-sheets, each containing four antiparallel β-strands, which were labeled as B to I ( Khayat et al., 2011 ). The residues between the β-strands form eight loops, among which the CD and C-terminal loops are exposed on the VLP exterior and can accommodate the insertion of short foreign peptides ( Liu et al., 2016 ; Wang et al., 2016 , 2018 ). The capsid protein was also reported to have the neutralizing and non-neutralizing epitope sites and the putative canonical HS-binding motif 98 IRKVKV 103 ( Mahe et al., 2000 ; Misinzo et al., 2006 ; Shang et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, experimental vaccines based on the chimeric viruses PCV1 and PCV2 were formulated in chimeric porcine circovirus-Cap proteins, where small Cap loops were replaced with other epitopes of interest. These chimeric proteins were expressed in Escherichia coli (E. coli), preserving the structure of the VLP [30][31][32], and this approach was demonstrated as an alternative against PCV2 infection.…”
Section: Introductionmentioning
confidence: 99%